Anti-freezing reversible bimetallic deposition electrochromic film and preparation method thereof

By introducing dual -metal ion hydraulic electrolytes in the reversible metal sedimentary electro -discolored film, the problem of incomplete circulation stability and low temperature tolerance in existing technologies, and achieve efficient and stable electro -discoloration effects.

CN119376153APending Publication Date: 2025-01-28OCEAN UNIV OF CHINA
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411958522.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28

Smart Images

  • Figure CN119376153A_ABST
    Figure CN119376153A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of electrochromic films, and particularly relates to an anti-freezing reversible bimetallic deposition electrochromic film and a preparation method thereof. The thin film comprises an M1M2 bimetal deposition layer, M1 is one of metals Cu, Ag and Pb, and M2 is one of metals Zn, Sn, Ni and Bi. A two-electrode system is adopted, heterogeneous metal ions are introduced, bimetallic ion hydrogel is constructed to serve as electrolyte, reversible deposition and dissolution of metal are controlled by adjusting voltage, and color change is achieved. The bimetallic film layer provided by the invention has a uniform and compact microstructure and can effectively isolate ultraviolet light, visible light and near-infrared light, and the transmissivity can be lower than 1%. When the material is applied to an electrochromic device, the material has quick response, excellent cycle stability and good low-temperature tolerance, and can promote the development of reversible deposition type electrochromic intelligent windows and other photoelectric application fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochromic film preparation, and in particular relates to an antifreeze type reversible bimetallic deposition electrochromic film and a preparation method thereof. Background Art

[0002] As an emerging technology that combines energy storage and optical adjustability, electrochromic film can undergo reversible changes in optical properties (transmittance, absorbance and reflectance) under external electric pulses, thereby achieving effective regulation of visible light and near-infrared light. It has attracted widespread attention in the fields of smart windows, optically tunable electronic components, portable electronic devices, and green energy-saving buildings.

[0003] Compared with the traditional embedding / de-embedding electrochromic film technology, the reversible metal deposition technology based on the reversible deposition / dissolution mechanism of metals has the electrochemical tunability of multiple optical states, wide-band modulation range, long durability and high contrast, making it an ideal choice in the field of smart windows. Due to the unique properties of metals, under the action of an applied voltage, the transparent conductive substrate can quickly change from a highly transparent state to an opaque state with a high extinction coefficient, effectively blocking sunlight and infrared radiation, thereby blocking the energy transfer between indoor and outdoor environments, achieving the best energy saving and dimming effects. In the existing reports on reversible metal deposition electrochromic films, single metal reversible deposition such as Zn, Cu, Ag, Au, etc. usually faces problems such as slow deposition kinetics, dendrites, and incomplete metal layer peeling, resulting in poor cycle stability and low dimming efficiency. In addition, although bimetallic reversible deposition such as CuBi, CuAu, NiCu, CuSn, etc. has a low nucleation potential and a fast response time, the commonly used liquid aqueous electrolytes usually have serious hydrogen evolution side reactions, and organic electrolyte solvents such as DMSO have poor low temperature resistance and easy leakage, resulting in decreased device stability and serious performance degradation. In contrast, aqueous gel electrolytes not only have ionic conductivity and transmission speed comparable to liquid electrolytes, but also provide good structural stability, mechanical strength and transparency.

[0004] Therefore, by introducing a heterogeneous metal ion and constructing a dual metal ion hydrogel electrolyte with high chemical stability, high transparency and high and low temperature tolerance to replace the traditional liquid electrolyte, a new idea is provided to solve the many difficulties faced in the development and practical application of reversible metal deposition electrochromic films. It is expected to obtain antifreeze reversible dual metal deposition electrochromic devices with high temperature applicability, high optical contrast, long-term cycle stability and fast switching capability. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an antifreeze-type reversible bimetallic deposition electrochromic film and a preparation method thereof, which adopts a two-electrode system, introduces heterogeneous metal ions and constructs a bimetallic ion hydrogel as an electrolyte, and achieves color change by adjusting the voltage to control the reversible deposition and dissolution of the metal.

[0006] The technical solutions adopted are: An antifreeze type reversible bimetallic deposition electrochromic film, the film comprising M 1 M 2 Bimetallic deposition layer, where M 1 M is one of the metals Cu, Ag, and Pb. 2 It is one of the metals Zn, Sn, Ni, and Bi. M can be adjusted as needed 1 With M 2 The molar ratio can be adjusted to achieve the adjustment of film color, etc.

[0007] Preferably, M 1 M 2 The bimetallic deposition layer is a CuZn bimetallic layer, or a CuBi bimetallic layer, or a CuSn bimetallic layer, or a PbSn bimetallic layer, or an AgNi bimetallic layer.

[0008] A method for preparing an antifreeze-resistant reversible bimetallic deposition electrochromic film comprises the following steps: (1) Clean and dry the working electrode and counter electrode; (2) M 1 、M 2 Soluble metal salts, potassium salts and hydrochloric acid are dissolved in water to prepare an electrodeposition precursor solution; (3) dissolving a monomer, an initiator and a cross-linking agent in water and heating the water to prepare a hydrogel; wherein the monomer is acrylic acid or acrylamide, the initiator is ammonium persulfate or potassium persulfate, and the cross-linking agent is diallylbenzene or N,N-methylenebisacrylamide; (4) immersing the hydrogel in an electrodeposition precursor solution to prepare a bimetallic ion hydrogel electrolyte; (5) The working electrode and the counter electrode are assembled as a two-electrode system with a bimetallic ion hydrogel as the electrolyte. An external bias voltage is applied and the reversible deposition and dissolution of the metal is controlled by adjusting the voltage to obtain a reversible bimetallic deposited electrochromic film.

[0009] Preferably, in step (1), the specific cleaning process is ultrasonic cleaning in deionized water, isopropanol and ethanol solutions for 10 to 15 minutes, and then drying.

[0010] Preferably, in step (1), the working electrode and the counter electrode are transparent conductive electrodes of fluorine-doped tin oxide (FTO) or indium-doped tin oxide (ITO).

[0011] Preferably, in step (2), the electrodeposition precursor solution is prepared at room temperature and mechanically stirred for 30 to 60 minutes.

[0012] Preferably, in the step (2), in the prepared electrodeposition precursor solution, M 1 The concentration of soluble metal salt is 0.004~0.04mol / L, M 2 The concentration of the soluble metal salt is 0.03~0.2 mol / L, the concentration of hydrochloric acid is 0.005~0.025 mol / L; the potassium salt is potassium nitrate or potassium chloride, and the concentration in the electrodeposition precursor solution is 0.2~1.0 mol / L.

[0013] Preferably, in step (3), the heating temperature is 60-80° C., and the heating process is 180-360 min.

[0014] Preferably, in step (4), the hydrogel is immersed in the electrodeposition precursor solution in a closed environment for 12 to 24 hours to prepare a dual metal ion hydrogel electrolyte.

[0015] Preferably, in step (5), the voltage applied is a negative voltage or a positive voltage, the negative voltage range is -0.8 to -1.0 V, and the positive voltage range is 3.0 to 4.0 V. When a certain negative voltage is applied, bimetallic deposition occurs on the working electrode, i.e., the coloring process; when a certain positive voltage is applied, bimetallic dissolution occurs on the working electrode, i.e., the fading process.

[0016] The film and the preparation method thereof of the present invention can be applied to the fields of smart windows, optically adjustable electronic components, portable electronic devices, green energy-saving buildings, etc.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The bimetallic film layer provided by the present invention has a uniform and dense microscopic morphology, can effectively block ultraviolet light, visible light and near-infrared light, and the transmittance can be less than 1%.

[0018] The reversible bimetallic deposition electrochromic film provided by the present invention is applied to an electrochromic device, which has a fast response (coloring time t c and fading time t b 14 s and 5 s, respectively) and excellent cycling stability.

[0019] The antifreeze reversible bimetallic deposited electrochromic film provided by the present invention has good low-temperature tolerance and can maintain relatively stable switching at -20°C. It is suitable for various application scenarios in most parts of the country and can promote the development of reversible deposited electrochromic smart windows and other optoelectronic application fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a microscopic morphology of the reversible bimetallic deposition electrochromic film prepared in Example 1.

[0021] Figure 2 The transmission spectra of the dual metal deposition electrochromic device prepared in Example 1 under negative voltage (coloring) and positive voltage (fading), respectively.

[0022] Figure 3 It is a comparison chart of the dynamic transmittance spectra of the metal layer deposited in Example 1 and Comparative Example 1; wherein Figure a is a dynamic transmittance spectrum chart of the single metal deposition in Comparative Example 1; and Figure b is a dynamic transmittance spectrum chart of the bimetallic reversible deposition prepared in Example 1.

[0023] Figure 4 These are the cycle stability test results of the bimetallic reversible deposition electrochromic device prepared in Example 1.

[0024] Figure 5 It is a comparison chart of the dynamic transmittance spectra of the bimetallic reversible deposition electrochromic device prepared in Example 1 at 0°C and -20°C; wherein, Figure c is the dynamic transmittance spectrum at 0°C; Figure d is the dynamic transmittance spectrum at -20°C. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and features of the present invention clearer, the present invention is further described in detail in conjunction with the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0026] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0027] Example 1

[0028] The Cu and Zn bimetallic reversibly deposited electrochromic thin films are prepared in the following steps: (1) The FTO electrode was ultrasonically cleaned with deionized water, isopropanol, and ethanol for 10 min, and then dried at 60 °C for 3 h.

[0029] (2) A Cu and Zn bimetallic reversible deposition precursor solution was prepared by adjusting the molar ratio of Cu to Zn to 1:5, dissolving copper chloride, zinc sulfate, potassium chloride, and hydrochloric acid in deionized water at concentrations of 0.04 mol / L, 0.2 mol / L, 1.0 mol / L, and 0.02 mol / L, respectively, and stirring the mixture to obtain an electrodeposition precursor solution.

[0030] (3) To prepare PAM hydrogel, acrylamide, N, N-methylenebisacrylamide, and potassium persulfate were dissolved in deionized water in a mass ratio of 85000:6:5, heated to 60°C, and kept warm for 180 minutes to obtain PAM hydrogel.

[0031] (4) Preparing a dual metal ion hydrogel electrolyte, the PAM hydrogel obtained above was immersed in the prepared electrodeposition precursor solution for 12 h to obtain a Cu, Zn dual metal ion hydrogel electrolyte.

[0032] (5) A two-electrode system was used, with FTO electrodes as the working electrode and the counter electrode, and the electrolyte was a CuZn bimetallic ion hydrogel electrolyte. A simple electrochromic smart window was assembled and an external bias voltage of -1.0 V was applied for coating. Under different voltages, a color-changing bimetallic reversibly deposited electrochromic film was obtained on the working electrode and the counter electrode.

[0033] Comparative Example 1

[0034] The Zn single metal reversible deposition electrochromic film is prepared in the following steps: (1) Cleaning and drying the FTO electrode, the specific process is the same as Example 1.

[0035] (2) A Zn single metal reversible deposition precursor solution was prepared by dissolving zinc sulfate, potassium chloride, and hydrochloric acid in deionized water at concentrations of 0.2 mol / L, 1.0 mol / L, and 0.02 mol / L, respectively, and stirring the mixture to obtain an electrodeposition precursor solution.

[0036] (3) To prepare PAM hydrogel, acrylamide, N, N-methylenebisacrylamide, and potassium persulfate were dissolved in deionized water in a concentration ratio of 85000:6:5, and the specific process was the same as in Example 1.

[0037] (4) Preparation of Zn single metal ion hydrogel electrolyte: Immerse the PAM hydrogel obtained above in the prepared electrodeposition precursor solution. The specific process is the same as that in Example 1.

[0038] (5) A two-electrode system is used, with FTO electrodes serving as the working electrode and the counter electrode, and a Zn single metal ion hydrogel electrolyte as the electrolyte, and then assembly is performed. The specific process is the same as in Example 1.

[0039] The performance of the bimetallic reversibly deposited electrochromic smart window and the single metal Zn deposited smart window obtained above were tested.

[0040] (1) The microscopic morphology of the deposited CuZn bimetallic was observed. Figure 1 As shown. Figure 1 It can be seen that the deposited CuZn bimetallic layer is uniform and dense, and has abundant nucleation sites.

[0041] (2) The transmission spectra of the CuZn bimetallic reversible deposition electrochromic smart window in both tinting and fading states were tested. The results are shown in Figure 2 As shown, under positive voltage, the transmittance of the device at 550 nm wavelength reaches 78%, and the CuZn bimetallic layer deposited under negative voltage can achieve an extremely low transmittance of less than 1% at 550 nm wavelength.

[0042] (3) Perform dynamic transmittance test on the electrochromic device and calculate the corresponding response time. Figure 3 As shown. The transmittance modulation range T 差 = Maximum transmittance - minimum transmittance, response time is T 差 The time it takes to change 90%. Figure 3 The transmittance modulation range of the CuZn bimetallic reversible deposition electrochromic device in Figure b reaches 57%, far exceeding Figure 3 The transmittance of pure zinc in Figure a (2%) is higher, and the response speed is faster (the coloring time tc and fading time tb are 14 s and 5 s, respectively), indicating that the CuZn bimetallic deposition has fast electrochemical reaction kinetics.

[0043] (4) The CuZn bimetallic reversible deposition electrochromic device was tested on a cycle basis. Figure 4 As shown, the CuZn bimetallic reversibly deposited electrochromic device has excellent cycle stability within 150,000 s (3,000 cycles), can maintain stable color switching, and the optical modulation range retention rate reaches 91%, indicating that the CuZn bimetallic reversibly deposited electrochromic device has excellent electrochemical stability.

[0044] (5) The dynamic transmission spectra of the gel and water-based CuZn bimetallic reversible deposition electrochromic smart windows were tested at different temperatures. The dynamic transmission spectra results are shown in Figure 5As shown in the figure, the CuZn bimetallic gel reversibly deposited electrochromic smart window can still maintain stable color switching at low temperatures of 0°C (Figure c) and -20°C (Figure d), indicating that the CuZn bimetallic gel reversibly deposited electrochromic smart window has excellent low temperature tolerance. However, the transmittance of the aqueous CuZn reversibly deposited electrochromic smart window remains basically unchanged at low temperatures (0°C and -20°C), and it cannot maintain normal operation. This is because there are a large number of free water molecules in the aqueous electrolyte, and the solvation of free water will hinder the transmission of ions in the electrolyte under low temperature conditions; while the large number of polymer chains in the gel electrolyte has a strong restrictive effect on free water, and at the same time has a desolvation effect on ions, which can ensure the stable transmission of ions in the electrolyte.

[0045] Example 2

[0046] Preparation of Cu, Bi bimetallic reversible deposition electrochromic thin film, the specific process is carried out according to the following steps: (1) Cleaning and drying the FTO electrode, the specific process is the same as Example 1.

[0047] (2) Prepare a Cu and Bi bimetallic reversible deposition precursor solution, adjust the molar ratio of the two metals to 1:10, dissolve copper chloride, bismuth chloride, potassium chloride, and hydrochloric acid in deionized water at concentrations of 0.02 mol / L, 0.2 mol / L, 0.5 mol / L, and 0.015 mol / L, respectively, and stir evenly to obtain an electrodeposition precursor solution.

[0048] (3) To prepare PAM hydrogel, acrylic acid, diallylbenzene, and ammonium persulfate were dissolved in deionized water in a concentration ratio of 85000:6:5, heated to 60°C, and kept warm for 180 minutes to obtain PAM hydrogel.

[0049] (4) Preparing a dual metal ion hydrogel electrolyte, the PAM hydrogel obtained above is immersed in a prepared electrodeposition precursor solution, and heated to obtain a Cu, Bi dual metal ion hydrogel electrolyte.

[0050] (5) A two-electrode system is used, with FTO electrodes as the working electrode and the counter electrode, and the electrolyte is a CuBi bimetallic ion hydrogel electrolyte, to assemble a simple electrochromic smart window, and an external bias voltage is applied to perform plating. Other parts not described are the same as in Example 1.

[0051] Under different voltages, bimetallic reversibly deposited electrochromic films with color change are obtained at the working electrode and the counter electrode. When used in electrochromic devices, they also have excellent electrochemical stability, low temperature tolerance and other excellent properties.

[0052] Example 3

[0053] Prepare Cu, Sn bimetallic reversible deposition electrochromic film, using ITO electrode as working electrode and counter electrode. Prepare Cu, Sn bimetallic reversible deposition precursor solution, adjust the molar ratio of the two metals to 1:3, dissolve copper chloride, tin chloride, potassium chloride, and hydrochloric acid in deionized water according to 0.01 mol / L, 0.03 mol / L, 0.2 mol / L, and 0.01 mol / L, and stir evenly to obtain an electrodeposition precursor solution. The electrolyte uses a CuSn bimetallic ion hydrogel electrolyte, and then assembles. Other places not mentioned are the same as Example 1.

[0054] Under different voltages, a bimetallic reversibly deposited electrochromic film with color change is obtained at the working electrode and the counter electrode.

[0055] Example 4

[0056] Prepare Cu, Pb bimetallic reversible deposition electrochromic film, using ITO electrode as working electrode and counter electrode. Prepare Cu, Pb bimetallic reversible deposition precursor solution, adjust the molar ratio of the two metals to 1:50, dissolve lead chloride, tin chloride, potassium chloride, and hydrochloric acid in deionized water according to 0.004 mol / L, 0.2 mol / L, 0.8 mol / L, and 0.025 mol / L, and stir evenly to obtain an electrodeposition precursor solution. The electrolyte uses a CuPb bimetallic ion hydrogel electrolyte, and then assemble. Other places not mentioned are the same as Example 1.

[0057] Under different voltages, a bimetallic reversibly deposited electrochromic film with color change is obtained at the working electrode and the counter electrode.

[0058] Example 5

[0059] Prepare Ag, Ni bimetallic reversible deposition electrochromic film, using FTO electrode as working electrode and counter electrode. Prepare Ag, Ni bimetallic reversible deposition precursor solution, adjust the ratio of the two metals to 1:10, dissolve silver nitrate, nickel nitrate, potassium nitrate, and hydrochloric acid in deionized water according to 0.02 mol / L, 0.2 mol / L, 0.8 mol / L, and 0.02 mol / L, and stir evenly to obtain an electrodeposition precursor solution. The electrolyte uses AgNi bimetallic ion hydrogel electrolyte, and then assembles. Other places not mentioned are the same as Example 1.

[0060] Under different voltages, a bimetallic reversibly deposited electrochromic film with color change is obtained at the working electrode and the counter electrode.

[0061] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. An antifreeze type reversible bimetallic deposition electrochromic film, characterized in that: The film includes a M1M2 bimetallic deposition layer, wherein M1 is one of the metals Cu, Ag, and Pb, and M2 is one of the metals Zn, Sn, Ni, and Bi.

2. The antifreeze reversible bimetallic deposition electrochromic film according to claim 1, characterized in that: The M1M2 bimetallic deposition layer is a CuZn bimetallic layer, or a CuBi bimetallic layer, or a CuSn bimetallic layer, or a PbSn bimetallic layer, or an AgNi bimetallic layer.

3. The method for preparing an antifreeze-type reversible bimetallic deposition electrochromic film according to claim 2, characterized in that: The steps include: (1) Clean and dry the working electrode and counter electrode; (2) Dissolve the soluble metal salts, potassium salts and hydrochloric acid of M1 and M2 in water to prepare an electrodeposition precursor solution; (3) dissolving a monomer, an initiator and a cross-linking agent in water and heating the water to prepare a hydrogel; wherein the monomer is acrylic acid or acrylamide, the initiator is ammonium persulfate or potassium persulfate, and the cross-linking agent is diallylbenzene or N,N-methylenebisacrylamide; (4) immersing the hydrogel in an electrodeposition precursor solution to prepare a bimetallic ion hydrogel electrolyte; (5) The working electrode and the counter electrode are assembled as a two-electrode system, and the bimetallic ion hydrogel is used as the electrolyte. An external bias voltage is applied, and the reversible deposition and dissolution of the metal is controlled by adjusting the voltage to obtain a reversible bimetallic deposition electrochromic film.

4. The method for preparing an antifreeze-type reversible bimetallic deposition electrochromic film according to claim 3, characterized in that: In the step (1), the specific cleaning process is ultrasonic cleaning in deionized water, isopropanol and ethanol solutions for 10 to 15 minutes, and then drying.

5. The method for preparing an antifreeze type reversible bimetallic deposition electrochromic film according to claim 3, characterized in that: In the step (1), the working electrode and the counter electrode are FTO or ITO transparent conductive electrodes.

6. The method for preparing an antifreeze-type reversible bimetallic deposition electrochromic film according to claim 3, characterized in that: In the step (2), the electrodeposition precursor solution is prepared at room temperature and mechanically stirred for 30 to 60 minutes.

7. The method for preparing an antifreeze type reversible bimetallic deposition electrochromic film according to claim 3, characterized in that: In the step (2), in the prepared electrodeposition precursor solution, the concentration of the M1 soluble metal salt is 0.004-0.04 mol / L, the concentration of the M2 soluble metal salt is 0.03-0.2 mol / L, and the concentration of the hydrochloric acid is 0.005-0.025 mol / L; the potassium salt is potassium nitrate or potassium chloride, and the concentration in the electrodeposition precursor solution is 0.2-1.0 mol / L.

8. The method for preparing an antifreeze-type reversible bimetallic deposition electrochromic film according to claim 3, characterized in that: In the step (3), the heating temperature is 60-80° C., and the heating process is 180-360 min.

9. The method for preparing an antifreeze type reversible bimetallic deposition electrochromic film according to claim 3, characterized in that: In the step (4), the mixture is immersed in a closed environment for 12 to 24 hours.

10. The method for preparing an antifreeze reversible bimetallic deposition electrochromic film according to claim 3, characterized in that: In the step (5), the applied voltage is a negative voltage or a positive voltage, the negative voltage range is -0.8~-1.0 V, and the positive voltage range is 3.0~4.0 V.

Citation Information

Patent Citations

  • Metal electro-deposition-based electro-variable emissivity device and preparation method

    CN111025812A

  • Color-variable electrochromic emissivity device and preparation method thereof

    CN111158201A

  • Multicolor electrochromic device and preparation method thereof

    CN113433751A

  • Preparation method of temperature-sensitive hydrogel and temperature-sensitive hydrogel product prepared by preparation method

    CN114058033A

  • Preparation method of bimetal center metal organic framework electrochromic film

    CN114105486A